1998
DOI: 10.1016/s0886-3350(98)80288-5
|View full text |Cite
|
Sign up to set email alerts
|

Is there a difference in incision healing based on location?

Abstract: The predominant factors in incision healing and stability were incision geometry, architecture, and location. Endothelial pump action was effective in removing fluid but was not effective in incision stability. Histological analyses confirmed that starting incisions in the vascular region (limbus) resulted in a fibroblastic response that enhanced incision stability and allowed rapid incision healing within 7 days postoperatively compared with the 60 days healing time required for incisions started in the avasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Ernest et al demonstrated that rectangular clear corneal incisions in feline eyes were less resistant to deformation than limbal incisions 11. Corneal incisions took 60 days to heal, while limbal incision healing occurred within 7 days due to the fibrovascular response.…”
Section: Discussionmentioning
confidence: 99%
“…Ernest et al demonstrated that rectangular clear corneal incisions in feline eyes were less resistant to deformation than limbal incisions 11. Corneal incisions took 60 days to heal, while limbal incision healing occurred within 7 days due to the fibrovascular response.…”
Section: Discussionmentioning
confidence: 99%
“…This might explain why we saw no improvement of corneal sensitivity on days 7 and 15, unlike the recovery of the scleral nerve system, which begins after 25 hours and achieves normal levels within 8-10 days. 17,18 In this study, the manual SICS procedure was mostly done on the right eye. Surgeons will usually use their right hand to make a 3.2-mm second port in the temporal site to ease surgical manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…Different factors can affect post-operative astigmatism: incision size and shape [3,8,[18][19][20], location relative to the limbus [4,6], suture technique and material [13]. Small-incision phacoemulsification may be associated with a lower surgically induced astigmatism, although it can lead to long-term flattening along the meridian of incision [7,10,18].…”
Section: Introductionmentioning
confidence: 99%